2014
DOI: 10.6000/1929-2279.2014.03.04.7
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Deficiency: A Causative Clue or a Sequel in Carboplatin Myelosuppression

Abstract: We have previously demonstrated that carnitine deficiency aggravated paracetamol-induced hepatopathy and carboplatin-induced nephropathy. As a continuum, we have addressed in the current study as to whether carboplatin-induced myelosuppression would be exacerbated by carnitine deficiency. Challenging male Wistar rats with a single dose of carboplatin (35 mg/kg, IP) induced bone marrow suppression manifested as anemia, leucopenia, thrombocytopenia as well as increased frequencies of the micronucleated bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…(17,18) It also seems that carboplatin may increase serum TNF-α, suppressing the development of hematologic progenitor cells. (19) Currently, genetic polymorphisms are being investigated to determine their association with paclitaxel-carboplatin hematologic toxicity, depending on race and ethnicity. The single nucleotide polymorphisms 2677G>T/A and 3435C>T of ABCB1 genes have been associated with neutropenia in paclitaxel chemotherapy in EOC cases in some studies, (20,21) but no association has been found in others.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) It also seems that carboplatin may increase serum TNF-α, suppressing the development of hematologic progenitor cells. (19) Currently, genetic polymorphisms are being investigated to determine their association with paclitaxel-carboplatin hematologic toxicity, depending on race and ethnicity. The single nucleotide polymorphisms 2677G>T/A and 3435C>T of ABCB1 genes have been associated with neutropenia in paclitaxel chemotherapy in EOC cases in some studies, (20,21) but no association has been found in others.…”
Section: Discussionmentioning
confidence: 99%